Effect of the EGTA (Ethylene Glycol Tetraacetic Acid) Supplementation in the Freezing Extender on Quality of Cryopreserved Bull Sperm - Posado R; García JJ; Gómez-Fernández J; Tomás C; Gómez-Izquierdo E; de Mercado E (International Journal of Veterinary Science and Research - Peertechz Publications, 2017)
The aim of this study was to evaluate the effect of the inclusion of divalent ion chelating agent EGTA (ethylene glycol tetraacetic acid) in the freezing extender on quality of cryopreserved bull sperm. The freezing extender (egg yolk Tris glycerol) was supplemented with 0 (non-supplemented), 1, 5, 10 and 15 mM EGTA. Bull sperm EGTA improved post thaw sperm quality but in different parameters according to the concentration of EGTA, 5 mM improved the acrosomal state and 1 mM the motility. Our results suggest the EGTA supplementation in the freezing extender of bull sperm might improve the post-thawing sperm quality.